Basic Principles and Scientific Importance of Reliability Theory - Verma A.; Vardhan A.S.S.; Bagana V.; Saket R.K.; Sanjeevikumar P. (My University, 2025)
This chapter elucidates the fundamental principles and the significant role of reliability theory in contemporary engineering and technology. In contemporary engineering and technology, reliability is a relatively recent topic. The drive toward enhanced reliability has been prompted by various factors. These factors encompass the rising intricacy and advancement of systems, heightened public consciousness regarding product excellence, emerging legal statutes addressing product accountability, contractual obligations from governments to adhere to reliability benchmarks, and financial incentives arising from the substantial expenses linked to failures, repairs, and warranty initiatives. Reliability plays a crucial role not only in the design phase of modern engineering but also in diverse areas such as life cycle costing, cost-benefit analysis, studies of operational capabilities, resource allocation for repairs and facilities, and the establishment of preventive maintenance protocols. A contemporary and trending perspective on reliability involves delving into the physics of failure processes, employing mathematical models to ascertain time to failure. This method necessitates a profound understanding of failure mechanisms and root causes. Mean time to failure is determined based on known or projected stresses, environmental factors, operational conditions, material characteristics, and component geometries. This section demonstrates the utilization of probabilistic methods, the application of fundamental principles in contemporary engineering facets, and industrial computational challenges. These collectively depict the scientific significance of reliability engineering. © 2024 by The Institute of Electrical and Electronics Engineers, Inc. All right reserved.